Impact of different strains of Bacillus spp. on the bulb production of Tulipa sintenisii Baker - Yenikalaycı, Ahmet (Frontiers in Plant Science, 2025)
As an ornamental plant, Tulipa sintenisii (Muş tulip) has great potential for potting and cut- flowers in floriculture. However, its low number of bulb production per plant is a major constraint to it becoming one of the common cultivated tulip species. This study was conducted to determine the impacts of 10 Bacillus species on bulb number increase as well as other plant parameters of T. sintenisii in the Mus province of Turkey in the 2020/2021 growing season. Selected, equally sized T. sintenisii bulbs were soaked with Bacillus spp. solution (3.4 × 107 CFU/cm3) for 2 s, and the inoculated bulbs were planted in the experimental field in autumn. The experiment was organized in a completely randomized block design with six replications. The investigated bulb parameters were taken at their physiological maturity. The tulip bulbs treated with Bacillus spp. had higher plant height (28.6 cm), bulb number/plant (2.25), total bulb weight (14.7 g), central bulb weight (13.1 g), central bulb length (40.9 mm), and central bulb diameter (26.8 mm) than the control treatment. The Bacillus strain EZF13 had the highest bulb number while EZF104 had the highest total bulb weight, central bulb weight, central bulb length, and central bulb diameter. These findings suggest that Bacillus treatment has great potential to increase bulb number per plant as well as other bulb parameters of native tulip species T. sintenisii. At the same time, an environmentally friendly production model was put forward without fertilizer application with bacteria application in tulips. At the same time, since the application of bacteria increases the usefulness of plant nutrients in the soil, it can be effective in reducing both the costs and the negative effects of fertilizers on the environment with less fertilizer use.